MAIN CHARACTERISTICS OF NATURAL GAS AND DRYING GAS BY ABSORPTION METHOD - Abdurakhmonov Shahzod Mahmudovich (Research Parks Publishing LLC, 2021)
The article presents an analysis of the main characteristics of natural gas, the density of natural gas in the gaseous state and its composition, methods of natural gas purification and gas dehydration by absorption. Plant includes gas separation unit, having at least one fractioning reservoir. Adsorption layers for adsorption kinetic separation are used in the separation unit. Adsorption layers release methane-rich flow of initial gas. Plant also includes refrigeration system with expander cycle of high pressure. Refrigeration system compresses the methane-rich gas flow to absolute pressure making more than approximately 1,000 pounds per square inch (6895 kPa). Refrigerating system also cools down the flow of methane-rich initial gas in one or more refrigerators and then extends the flow of cooled natural gas, forming a flow of liquefied product. Methods of initial natural gas flow liquefaction using AKP and refrigerating system with expander cycle of high pressure are also proposed in this invention.